Trabalhadores descarregando carroça em armazém (Museu Afro-Digital, 2025)
Collection: Trabalho negro na Bahia
Keywords: Working class--Brazil--History; Black people--Brazil--History; Black people--Brazil--Social conditions; Black Workers; Labour History